The relationships between the average semester growth rates of lexical sophistication in L2 English writing at secondary school: A learner corpus analysis - ROKOSZEWSKA, KATARZYNA (Glottodidactica, 2021)
In line with Complex Dynamic Systems Theory (CDST), the aim of the paper is to examine dynamics and causality among the growth rates of lexical sophistication in L2 writing development. The study was based on The Written English Developmental Corpus of Polish Learners (WEDCPL) which consists of over 1,900 essays composed during 21 repeated measurements by 100 learners over three years (2014–2017) at secondary school. Lexical sophistication, operationalised as different frequency levels, was analysed with the Lextutor software (Cobb 2014). The results indicated that the learners relied on the first frequency level. The monthly growth rates (MGRs) of the frequency levels were variable but no significant peaks were registered. The relationships between the average semester growth rates (ASGRs) revealed competition between the first and higher frequency levels, and some support between the higher levels. Thus, developing learners’ lexis beyond the first level counteracts the production of lexically unsophisticated texts and supports the use of more advanced words.